Characterising the structural brain connectome in Alzheimer's disease and its relation to cognitive intra-individual variability. - Lee, Shao-Hsuan Stephanie (Department of Human Biology, 2023)
Research on Alzheimer's disease (AD) has shown white matter (WM) degeneration and structural connectome disruptions measured by diffusion tensor imaging (DTI) as well as increased reaction time intra-individual variability (RT IIV) on neurocognitive testing. However, the relationship between these changes measured on these different modalities remains unexplored. To explore possible relationships between these alterations, this study used tractography to identify WM changes, as indexed by fractional anisotropy (FA) and mean diffusivity (MD), followed by a graph theory-based analysis of the brain structural connectome, and investigated the relationship between these graph theory metrics and RT IIV in 16 AD patients and 20 healthy elderly controls. Within AD patients, we identified WM tracts with lower FA and higher MD mostly located in the cortical and subcortical temporal lobes, such as the hippocampus subregions, compared to healthy elderly controls. We also observed higher FA in the WM tracts within the thalamus as well as between the thalamus and brainstem in AD patients. In the structural brain connectome of these patients, there were regions with altered nodal strength, transitivity, and local efficiency relative to the controls' connectome. Conversely to many studies, we found increases in nodal efficiency across multiple regions and higher global efficiency in AD patients compared to healthy elderly controls. Finally, higher global efficiency was correlated with increased RT IIV on the CRT task in AD patients. In AD, a positive relationship between transitivity in the left cingulate cortex and RT IIV as well as between nodal efficiency in the left cortical temporal lobe and mean RT on the CRT task were observed. On the other hand, lower transitivity in the right thalamus and increased RT IIV, as well as lower transitivity and longer mean RT were found on both the SRT and CRT tasks in AD patients. Our results may show evidence of disruptions and compensatory mechanisms in WM tracts and network metrics in AD. Together, these results revealed WM changes, topological alterations of the brain structural connectome in AD and that these findings can be used in combination with IIV to predict cognitive decline or progression of AD.